Flexible and Stretchable Micromagnet Arrays for Tunable Biointerfacing. (23rd December 2014) - Tseng, Peter; Lin, Jonathan; Owsley, Keegan; Kong, Janay; Kunze, Anja; Murray, Coleman; Di Carlo, Dino
<x xml:space="preserve">Abstract</x> A process to surface pattern polydimethylsiloxane (PDMS) with ferromagnetic structures of varying sizes (micrometer to millimeter) and thicknesses (>70 μm) is developed. Their flexibility and magnetic reach are utilized to confer dynamic, additive properties to a variety of substrates, such as coverslips and Eppendorf tubes. It is found that these substrates can generate additional modes of magnetic droplet manipulation, and can tunably steer magnetic‐cell organization. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>